HANSEN`S DISEASE IN CHILDREN UNDER 15 YEARS OLD: SOCIODEMOGRAPHIC AND CLINICAL CHARACTERIZATION OF THE CASES IN A HYPERENDEMIC MUNICIPALITY - Silva, Francisca Jade Lima de Andrade; de Aquino, Dorlene Maria Cardoso; Monteiro, Estela Maria Leite Meirelles; Coutinho, Nair Portela Silva; Corrêa, Rita da Graça Carvalhal Frazão; Paiva, Maria de Fátima Lires (Cogitare Enfermagem, 2022)
Objective: to analyze the sociodemographic and clinical profile of reported cases of Hansen´s disease in children under 15 years old in the municipality of São Luís - Maranhão - Brazil. Method: descriptive study conducted with 826 cases reported in the Notifiable Diseases Information System, in São Luís - Maranhão, in the period from 2010 to 2019. Data were analyzed using descriptive statistics and were expressed in absolute and relative frequencies. Results: age group between 10 and 14 years (60.29%), male (51.09%), brown (69.59%), incomplete elementary education (39.58%), multibacillary (62.71%), dimorphic clinical form (54.24%), up to five lesions (74.45%), zero to two nerves affected (83.23%), no bacilloscopic (46.28%), new cases (93.70%), spontaneous demand (46.38%) and zero degree of disability at diagnosis (78.98%). Conclusion: hyper-endemic parameters with high risk for the disease were demonstrated. It is important to create control and prevention strategies to reduce Hansen´s disease transmission in children.